The Future Network Research Based on Reconfiguration and Expansible - You Dai; Bin Zhuge; Huanhuan Song; Weiming Wang; Julong Lan (Institute of Advanced Engineering and Science, 2013)
With the development of network, the internet has more and more problems. Ubiquitous information services, diversified and comprehensive network business, different business may have different QoS requirements, and the safety credible information interaction, etc., these problems raise huge challenges to the supporting capacity of current network architecture system. Therefore, we should study out new future network architecture to meet the requirements of users. In this paper, we present a new network architecture based on reconfigurable and expansible, the core idea is to provide logic bearing networks with different QoS guarantees for different service. The architecture uses virtualization technology to abstract and divide the network resources, divide the network function module into business layer, ATS layer and ATC layer three functional surfaces from the point of view of whole network reconfiguration. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3425